The Prevention and Treatment of Atherosclerosis (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This special issue of JCM ‘The Prevention and Treatment of Atherosclerosis’ will walk the Readers across novel diagnostic achievements in atherosclerosis and contemporary actions towards optimizing therapy.Everything begins with diagnosis. Accurate diagnostic tools and tests are of utmost importance. Contemporary research on microparticles, non-coding RNAs, proteomic characterization, …, offers detailed molecular characteristics of athero-thrombosis.Prevention is equally important as treatment. The impact of eating habits in prophylaxis of many pathologies, including cardiovascular disease has been documented.Then new pharmacological agents. Managing hypercholesterolemia with PCSK9 inhibitors, shown great potential in efficient lipid lowering to achieve LDL-C treatment goals, as well as reduction in cardiovascular mortality and morbidity.However, therapeutic goals accomplishment requires supervision. Arising number of data support that cardiovascular risk prediction can be improved with imaging modalities displaying atheroma: carotid plaque ultrasonography, coronary calcium score, intravascular ultrasonography, and optical coherent tomography or many others.As atherosclerosis is a progressive disease, it comes the time for more radical management, including endovascular and surgical intervention. There is field for new stent and equipment technologies, new surgical and endovascular techniques, supervision of endovascular procedures with IVUS, OCT, functional flow assessment or cell therapy.From diagnosis to risk stratification, elaborated prevention models, finally to modern and optimized therapeutic intervention.